Mutagenic potential of Cordia ecalyculata alone and in association with Spirulina maxima for their evaluation as candidate anti-obesity drugs - Araldi, Rodrigo Pinheiro [UNESP]; Rechiutti, Bruna Mendes [UNESP]; Mendes, Talita Biude [UNESP]; Ito, Eliana Tiemi [UNESP]; Souza, Edislane Barreiros de [UNESP] (Funpec-editora, 2014)
Obesity is one of the most important nutritional disorders, and can be currently considered as an epidemic. Although there are few weight reduction drugs available on the market, some new drug candidates have been proposed, including Cordia ecalyculata, a Brazilian plant with anorectic properties, and Spirulina maxima, a cyanobacterium with antioxidant and anti-genotoxic activity. In this study, we evaluated the mutagenic potential of C. ecalyculata at doses of 150, 300, and 500 mg/kg alone and in association with S. maxima at doses of 75, 150, and 250 mg/kg, respectively, through an in vivo micronucleus test, using mice of both sexes, and an in vitro micronucleus test and comet assay, using human peripheral blood. For all tests, cyclophosphamide was used as a positive control. The results showed that treatment of 300 mg/kg C. ecalyculata and the combination treatment of 500 mg/kg C. ecalyculata with 250 mg/kg S. maxima resulted in anorectic effects. The mutagenic tests did not reveal any clastogenic or genotoxic activity for any treatment, indicating that these candidates could be marketed as weight-reduction drugs. Moreover, the drugs contain chemo-preventive substances that can protect against tumorigenesis, which has been associated with obesity.
Keywords: Cordia ecalyculata; Spirulina maxima; Micronucleus; Comet assay; Mutagenesis